Quantitative real-time PCR assays for species-specific detection and quantification of Baltic Sea spring bloom dinoflagellates - Brink, Annica Marie; Kremp, Anke; Gorokhova, Elena (Frontiers in Microbiology, 2024)
In the Baltic Sea, the dinoflagellates Apocalathium malmogiense, Biecheleria baltica, and Gymnodinium corollarium are important contributors to the spring bloom. However, their relative contribution to the bloom community cannot be unambiguously determined by conventional light microscopy due to a lack of resolution of distinctive morphological features of the three species.Here, we describe a molecular approach based on a quantitative real-time polymerase chain reaction (qPCR) primer and probe system, targeting the ITS1 and ITS2 regions of the rRNA gene for all three species and enabling their quantification. The specificity of the method was demonstrated using monocultures of A. malmogiense, B. baltica, G. corollarium as well as three other dinoflagellate species co-occurring in the Baltic Sea during spring and validated using fieldcollected phytoplankton samples.